For $\alpha \in \mathbb{R}$, define $\displaystyle I(\alpha):=\int_{0}^{2\pi}e^{\alpha \cos \theta}\cos(\alpha \sin \theta)\; d\theta$. Calculate $I(0)$. Hence evaluate $\displaystyle\int_{0}^{2\pi}e^{\cos \theta}\cos( \sin \theta)\; d\theta$.

Hint: To evaluate the integral that expresses $\displaystyle\frac{dI}{d\alpha}$, consider $\displaystyle\frac{\partial}{\partial \theta}(e^{\alpha \cos \theta}\sin(\alpha \sin \theta))$.

How do I do this question? I think this might have something to do with the Fundamental Theorem of Calculus, but I'm not sure.

I computed $\displaystyle I(0)=\int_{0}^{2\pi} d\theta=2 \pi$, and $\displaystyle I(1)=\int_{0}^{2\pi}e^{\cos \theta}\cos( \sin \theta) d\theta$. Following the hint I get

$$\begin{align} \frac{\partial}{\partial \theta}(e^{\alpha \cos \theta}\sin(\alpha \sin \theta)) & =\alpha e^{\alpha \cos \theta} \sin (\alpha \sin \theta) + e^{\alpha \cos \theta}\cos(\alpha \sin \theta) \alpha \cos \theta \\ & = \alpha e^{\alpha \cos \theta} \sin (\alpha \sin \theta) + \frac{dI}{d \alpha} \cos \theta. \\ \end{align}$$

Is this correct so far?

The answers in the question referred as a duplicate does not help. I'm in a course dealing with real values, not complex.

  • 1
    $\begingroup$ Shouldn't $I(0)=\int_0^{2\pi}e^0\cos(0)d\theta$? $\endgroup$ Jun 2, 2013 at 9:43
  • $\begingroup$ @GitGud Is there any way I could do this question another way than the one you have answered? I haven't reached that stage in my course. $\endgroup$
    – user4167
    Jun 2, 2013 at 9:46
  • 2
    $\begingroup$ you should take the hint. do the derivative they tell you to do, and see if it relates anyway to your integrand... $\endgroup$ Jun 2, 2013 at 9:47
  • $\begingroup$ @user4167 Have you read the other answers? Also are you sure you're supposed to do this without the tools I used? $\endgroup$
    – Git Gud
    Jun 2, 2013 at 9:50
  • 1
    $\begingroup$ @user4167 OK. You should specify that in your question stating that the answers in the duplicate do not help, so your question doesn't get closed. $\endgroup$
    – Git Gud
    Jun 2, 2013 at 9:57

6 Answers 6


First a correction:

$$\begin{align} \frac{\partial}{\partial \theta}(e^{\alpha \cos \theta}\sin(\alpha \sin \theta)) & =-\alpha \sin \theta \, e^{\alpha \cos \theta} \sin (\alpha \sin \theta) + e^{\alpha \cos \theta}\cos(\alpha \sin \theta) \alpha \cos \theta \\ \end{align}$$

Now \begin{align} \frac{dI}{d\alpha}&=\frac{d}{d\alpha}\int_{0}^{2\pi}e^{\alpha \cos \theta}\cos(\alpha \sin \theta) d\theta \\ &=\int_{0}^{2\pi}\frac{d}{d\alpha}(e^{\alpha \cos \theta}\cos(\alpha \sin \theta)) d\theta \\ &=\int_{0}^{2\pi}\cos \theta \, e^{\alpha \cos \theta}\cos(\alpha \sin \theta)- e^{\alpha \cos \theta}\sin(\alpha \sin \theta)\sin \theta \, d\theta \\ &=\int_{0}^{2\pi}\frac{1}{\alpha} \frac{\partial}{\partial \theta}(e^{\alpha \cos \theta}\sin(\alpha \sin \theta)) d\theta \\ &=\frac{1}{\alpha} \Big[e^{\alpha \cos \theta}\sin(\alpha \sin \theta)\Big]_0^{2\pi} \\ &=0 \end{align}

So $I(\alpha)$ is actually constant.

So $I(1)=I(0)=2\pi$

So the answer is $2\pi$

  • $\begingroup$ Very nice solution john. $\endgroup$
    – juantheron
    Oct 24, 2016 at 6:24

Alternatively, we know that $$\Re\left( e^{\Large e^{i\theta}}\right)=e^{\cos\theta}\cos(\sin\theta)$$ Using Taylor series of exponential function and Euler's formula we have $$e^{\Large e^{i\theta}}=1+(\cos\theta+i\sin\theta)+\frac{(\cos2\theta+i\sin2\theta)}{2!}+\frac{(\cos3\theta+i\sin3\theta)}{3!}+\cdots$$ Using $\displaystyle\int_0^{2\pi}\cos(n\theta)\;d\theta=0$ for $n$ is integer and $n\neq0$, we get $$\begin{align}\int_0^{2\pi}e^{\cos\theta}\cos(\sin\theta)\;d\theta&=\int_0^{2\pi}\Re\left( e^{\Large e^{i\theta}}\right)d\theta\\&=\int_0^{2\pi}\left(1 +\cos\theta+\frac{\cos2\theta}{2!}+\frac{\cos3\theta}{3!}+\cdots\right)d\theta\\&=2\pi\end{align}$$

  • 3
    $\begingroup$ Nice solution, I love it! :) $\endgroup$ Nov 18, 2014 at 18:52
  • 2
    $\begingroup$ Thanks @Anastasiya-Romanova. I'm glad you like it :-) $\endgroup$
    – Venus
    Nov 19, 2014 at 5:48

Rewrite $$ \int_0^{\large2\pi} e^{\cos\theta}\cos(\sin\theta)\ d\theta=\Re\left[\int_0^{\large2\pi} e^{\Large e^{i\theta}}d\theta\right]. $$ Let $$ I(\alpha)=\int_0^{\large2\pi} e^{\Large\alpha e^{i\theta}}d\theta, $$ then $$ \frac{dI}{d\alpha}=I'(\alpha)=\int_0^{\large2\pi} e^{i\theta}e^{\Large\alpha e^{i\theta}}d\theta. $$ Rewrite $$ I'(\alpha)=\frac{1}{i\alpha}\int_0^{\large2\pi} i\alpha e^{i\theta}e^{\Large\alpha e^{i\theta}}d\theta. $$ Let $x=\alpha e^{i\theta}\;\color{blue}{\Rightarrow}\;dx=i\alpha e^{i\theta}\ d\theta$, then $$ I'(\alpha)=\frac{1}{i\alpha}\left[e^{\Large\alpha e^{i\theta}}\right]_{\theta=0}^{\large2\pi}=0. $$ Thus $\Re\left[I'(\alpha)\right]=0$ and $I(\alpha)$ is a constant. Taking $\alpha=0$ yields $I(0)=2\pi$. Hence $\color{blue}{I(\alpha)=2\pi}$ and consequently $$ \int_0^{\large\pi} e^{\cos\theta}\cos(\sin\theta)\ d\theta=\large\color{blue}{2\pi}. $$


I simplified my approach.

As a generalization of Venus' answer , assume that $\alpha$ is a positive real number and that $f(z)$ is an entire function.

Then $$ \begin{align} \int_{0}^{2 \pi} \left( f(\alpha e^{i\theta})+f(\alpha e^{-i \theta}) \right) \, \mathrm d \theta &= \int_{0}^{2 \pi} \left(\sum_{n=0}^{\infty} \frac{f^{(n)}(0)}{n!} (\alpha e^{i \theta})^{n} + \sum_{n=0}^{\infty}\frac{f^{(n)}(0)}{n!} (\alpha e^{-i \theta})^{n} \right) \, \mathrm d \theta \\ &= 2\int_{0}^{2 \pi} \sum_{n=0}^{\infty} \frac{f^{(n)}(0)}{n!} \alpha^{n} \cos(n \theta) \, \mathrm d \theta \\ &= 2\sum_{n=0}^{\infty} \frac{f^{(n)}(0)}{n!} \, \alpha^{n} \int_{0}^{2 \pi} \cos (n \theta) \, \mathrm d \theta \\ &= 2 f(0) \int_{0}^{2 \pi} \, d \theta + 2 \sum_{n=1}^{\infty}\frac{f^{(n)}(0)}{n!} \, \alpha^{n} \int_{0}^{2 \pi} \cos (n \theta) \, \mathrm d \theta \\ &=4 \pi f(0) + 2\sum_{n=1}^{\infty}\frac{f^{(n)}(0)}{n!} (0) \\ &= 4 \pi f(0). \end{align}$$

If we let $f(z) = e^{z}$, we get $$ 2 \int_{0}^{2 \pi} e^{\alpha \cos \theta} \cos (\alpha \sin \theta) \, \mathrm d \theta = 4 \pi (1) = 4 \pi.$$

And if we let $f(z) = \cos(z)$, for example, we get $$2 \int_{0}^{2 \pi} \cos (\alpha \cos \theta) \cosh(\alpha \sin \theta) \, \mathrm d \theta = 4 \pi (1) = 4 \pi.$$

  • 1
    $\begingroup$ Please give me some more information about your well known Fourier series! $\endgroup$
    – FreeMind
    Dec 16, 2014 at 7:21
  • 2
    $\begingroup$ @FreeMind $$ \begin{align} \sum_{k=0}^{\infty} b^{k} \cos(k \theta) &= \text{Re} \sum_{k=0}^{\infty} b^{k} e^{ik \theta} = \text{Re} \sum_{k=0}^{\infty} (be^{i \theta})^{k} \\ &= \text{Re} \ \frac{1}{1-be^{i \theta}} \\ &= \text{Re} \ \frac{1-be^{-i \theta}}{(1-be^{i \theta})(1-be^{-i \theta})} \\ &= \text{Re} \ \frac{1- b \cos \theta + i b \sin \theta}{1 - 2 b \cos \theta + b^{2}} \\ &=\frac{1- b \cos \theta}{1-2b \cos \theta + b^{2}} \end{align}$$ $\endgroup$ Dec 16, 2014 at 8:15
  • 1
    $\begingroup$ @FreeMind I don't know of a list, but basically any related series can be derived by differentiating or integrating the series in my post or the series $$\sum_{k=0}^{\infty} b^{k} \sin(k \theta) = \frac{b \sin \theta}{1-2b \cos \theta + b^{2}} \ , \ |b| <1$$ with respect to $\theta$. For example, integrating the above series with respect to $\theta$ we get $$\sum_{k=1}^{\infty} \frac{b^{k} \cos (k \theta)}{k} = - \frac{1}{2} \log \left(1- 2 b \cos \theta + b^{2} \right) \ , \ |b| <1.$$ $\endgroup$ Dec 17, 2014 at 6:31
  • 1
    $\begingroup$ Have any idea about, math.stackexchange.com/questions/1070144/… $\endgroup$
    – FreeMind
    Dec 17, 2014 at 11:00
  • 1
    $\begingroup$ @Machinato Alternatively, you can use the residue theorem. $$\operatorname{Re} \int_{0}^{2 \pi} f(e^{i \theta}) \, d \theta = \text{Re} \int_{|z|=1} \frac{f(z)}{iz} \, dx = \operatorname{Re} \left(2 \pi i \operatorname{Res}\left[\frac{f(z)}{iz},0 \right]\right)=2 \pi f(0)$$ I wanted to generalize the other answer without using contour integration. $\endgroup$ Jun 8, 2017 at 16:43

Here is a solution using real analysis, different from solutions already published (involving derivation under integral sign, series, etc.). This solution is based on a connection with cardinal sine function.


$$f(x):=e^{-\cos x} \cos(\sin x)$$

It is periodic function with the following graphical representation:

enter image description here

As it is symmetrical with respect to vertical line $x=\pi$, it is sufficient to be able to compute

$$I_1:=\int_0^{\pi/2} f(x)dx \ \ \text{and} \ \ I_2:=\int_{\pi/2}^{\pi} f(x)dx$$

The result will be $2(I_1+I_2)$.

Preliminary result:

$$\int^{\color{red}{\pi/2}}_0 e^{-p\cos x} \cos(p\sin x)\,dx=\int^{\infty}_p \frac{\sin(t)}{t}dt\tag{1}$$

which is formula NT 13(26) page 486 of my 1980 edition of Gradshteyn and Ryzhik.

(where we recognize the opposite of a primitive function of cardinal sine function).

  • Integral $I_1$ has the following expression by taking $p=-1$ in (1):

$$I_1=\int^{\infty}_{-1} \frac{\sin(t)}{t}dt\tag{2}$$

  • It is now sufficient to establish that :

$$I_2=\int_{-\infty}^{-1} \frac{\sin(t)}{t}dt\tag{3}$$

In this way, we will have $2(I_1+I_2)=2\int_{-\infty}^{+\infty} \frac{\sin(t)}{t}dt=2 \pi$

by using the classical result $\int_{-\infty}^{\infty} \dfrac{\sin(x)}{x}dx=\pi.$

Here is the proof of (3):

$$I_2:=\int_{\pi/2}^{\pi} f(x)dx \ \ \overset{x:=\pi-X}{=} \ \ -\int_{\pi/2}^{0} e^{-\cos(X)}\cos(\sin(X))dX$$

$$I_2=\int_0^{\pi/2} e^{-\cos(X)}\cos(\sin(X))dX$$

Using (1) with $p=1$:

$$I_2=\int_1^{\infty} \frac{\sin(t)}{t}dt$$

It remains to take the change of variable $T=-t$ to obtain the desired result (3).


Let: $\displaystyle \tag*{} I(n,t) = \int \limits_{0}^{2 \pi} e^{t \cos \theta} \cos( n \theta - t\sin \theta) \mathrm{d \theta}$ $\displaystyle \tag*{} I(n,1) = \int \limits_{0}^{2 \pi} e^{ \cos \theta} \cos( n \theta - \sin \theta) \mathrm{d \theta}$ On differentiating both the sides, we have: $\displaystyle \tag*{} I'(n,t) = \int \limits _{0}^{2 \pi} \dfrac{\partial( e^{t \cos \theta} \cos( n \theta - t\sin \theta))}{\partial t} \mathrm{d \theta}$ We have:

$\displaystyle \tag*{} \dfrac{\partial( e^{t \cos \theta} \cos( n \theta - t\sin \theta))}{\partial t} = e^{t \cos \theta} \left [(\cos (n \theta - t\sin \theta))(\cos \theta) + (\sin (n \theta - t \sin \theta))(\sin \theta)\right ]$

Using the basic trigonometric identity, which states,

$\displaystyle \tag*{} \cos (A-B) = \cos A \cos B + \sin A \sin B$ We obtain: $\displaystyle \tag*{} \dfrac{\partial( e^{t \cos \theta} \cos( n \theta - t\sin \theta))}{\partial t} = e^{t \cos \theta} \cos ((n-1) \theta - t \sin \theta)$ Notice that: $\displaystyle \tag{1} I'(n,t) = I(n-1,t)$ Now, let’s derive some useful solutions $\displaystyle \tag{2} I(0,0) = \cos(0)\int \limits _{0}^{2 \pi} \mathrm{d \theta} = 2 \pi$ and $\displaystyle \tag{3} I(n,0) = \int \limits _{0}^{2 \pi} \cos (n \theta) \mathrm{d \theta} = 0$ Now, note that: $\displaystyle \tag*{} \int \limits _{0}^{t} I'(n,t) = \int \limits _{0}^{t} I(n-1,a) \mathrm{ da}$ $\displaystyle \tag*{} I(n,t) - \underbrace{I (n,0)}_{=0} = \int \limits _{0}^{t} I(n-1,a) \mathrm{ da}$ $\displaystyle \tag{4} I(n,t) = \int \limits _{0}^{t} I(n-1,a) \mathrm{ da}$ Now, to find $I'(0,t)$, to find this, I am going to rename the variable to apply differentiation under integral once again! Let: $\displaystyle \tag*{} I(s) = \int \limits _{0}^{2 \pi} e^{s \cos \theta} \cos (-s \sin \theta) \mathrm{ d \theta}$ $\displaystyle \tag*{} I'(s) = \int \limits _{0}^{2 \pi} \dfrac{\partial (e^{s \cos \theta}\cos (-s \sin \theta))}{\partial s} \mathrm{d \theta}$ $\displaystyle \tag*{} \dfrac{\partial (e^{s \cos \theta}\cos (s \sin \theta))}{\partial s} \mathrm{d \theta} = e^{s \cos \theta} \cos (\theta - s \sin \theta)$ and $\displaystyle \tag*{} e^{s \cos \theta} \cos (\theta - s \sin \theta) \cdot s = \dfrac{\partial(e^{s \cos \theta} \sin (s \sin \theta))}{\partial \theta}$ $\displaystyle \tag*{} I(s) = \dfrac{1}{s} \int \limits _{0} ^{2 \pi} \partial( e^{s \cos \theta} \sin ( s \sin \theta)) = 0$ Now, so $I'(0,t) = 0$ , so why not plug this into $(4)$, we get:

$\displaystyle \tag*{} \begin{align} I(0,t)&=2\pi \\\\ I(1,t) &= 2\pi\cdot t \\\\ I(2,t) &= 2 \pi \cdot \dfrac{t^2}{2!} \\\\ I(n,t) &= 2\pi \cdot \dfrac{t^n}{t!} \end{align}$ and $\displaystyle \tag*{} I(n,1) = 2 \pi \cdot \dfrac{1^n}{t!}$ Hence, $\displaystyle \tag*{} \boxed{\boxed{ \int \limits_{0}^{2 \pi} e^{ \cos \theta} \cos( n \theta - \sin \theta) \mathrm{d \theta} = \dfrac{2 \pi}{n!}}}$

Now, since $\cos x$ is even function, we have $\cos(-\sin x) = \cos(\sin x)$. So we have:

$\displaystyle \tag*{} \boxed{\boxed{ \int \limits_{0}^{2 \pi} e^{ \cos \theta} \cos(- \sin \theta) \mathrm{d \theta}=2 \pi= \int \limits_{0}^{2 \pi} e^{ \cos \theta} \cos(\sin \theta) \mathrm{d \theta}}}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.